FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKTIVITAS TENAGA KERJA PADA USAHA KECIL DAN MIKRO - KHAERUMAN (AKADEMIKA, 2018)
This research goal to be achieved is to know the factors that affect labor productivity and to know what efforts are done by small businesses to improve labor productivity especially in Pd. Jujur Lestari. The method used in this research is qualitative method with data technique such as; interviews, and documentation. These are the research subjects of Owner and Employee Pd. Jujur Lestari. Based of present of study, than influence factors in Pd. Jujur Lestari have know, that are internal factors and external factors. Internal factors are included age, education rate, health, and skill. External factors are included compatible wages gift. Appropriate decision of wages system, tools, health communication pattern, conducive place, health and disaster subsidies cost attestation of manager to the employees, good arrangement problem by manager. Efforts done by micro industries to increase productivity of employees by Pd. Jujur Lestari are 1) to give a conformity appreciation to excellent employees. 2) analyze the grade employees’ productivity every month. 3) stimulate CEO in order to they can work with employees. 4) schedule un equal activity that can increase approximation of employees interpersonal connection. Like traveling, out born and tassakuran. 5) to create harmonic communication at work. 6) create design of problem or conflict solving with family relation. 7) clear employees working that mean to clear standard of the employees working resources. 8) Increase discipline of working. 9) Increase employee ability with un equal practice. 10) create working conditions and healthy communication design. 11) Conformity salary system application. 12) to published whole working system that can do in house or in company.